Analysis of factors influencing influenza outbreaks in schools in Taicang City, China - Shi, Yao; Xu, Lei; Jiang, Hai; Cai, Yongbin; Bao, Changjun; Liu, Wendong (Frontiers in Public Health, 2024)
Objective: This study aims to analyze the awareness of influenza prevention and control and the behavioral attitudes toward the work among parents and staff in schools in Taicang City and the impact of the vaccination rate among students on influenza outbreaks in schools. The findings can provide references for the development of effective control strategies for the spread of influenza.Method: An anonymous questionnaire survey was conducted on 10,962 students from 20 schools in Taicang City, with class as the unit of analysis. The survey investigated their awareness of influenza prevention and control, their attitudes, and the vaccination coverage.From January to June 2023, a total of 388 influenza outbreaks were reported in schools in Taicang City, involving 77 schools. There were 3,475 confirmed cases, with an average infection rate of 18.53%. In schools where influenza outbreaks had occurred, the incidence rate of those who received influenza vaccine was significantly lower than those who did not, and the vaccine protection rate was 28.22%. The knowledge awareness rates of "the main transmission routes of influenza" and "influenza vaccination can prevent influenza" among parents of students were 95.49% and 93.16%, respectively. The correct attitudes of parents towards "actively reporting relevant symptoms to teachers when their children show symptoms" and "avoiding classes with diseases when their children are suspected to be sick" are 98.80% and 96.26%, respectively. The differences between schools with and without epidemic are statistically significant (P<0.05). The correct attitudes of the class teacher towards "correct management and control of students with flu like symptoms in the class" and "taking correct prevention and control measures in the event of a flu epidemic in the class" were 89.36% and 92.55%, respectively. The differences between epidemic related and non epidemic related classes were statistically significant (P<0.05).Enhance the knowledge level of influenza prevention and control among parents of students, Strengthening the training for class teachers in emergency response to infectious diseases and increasing vaccination coverage among students can effectively reduce the incidence of influenza and thereby the occurrence of cluster outbreaks in schools.